Climate Change and Health: Impacts, Adaptation, and Public Health Strategies - Adedeji Rog Fuerth; Betrò Karlin; Hamlet Patz Jr; Humala Simangunsong (Intitute of Computer Science (IOCS), 2021)
Climate change poses a multifaceted threat to human health, with far-reaching consequences that extend beyond immediate impacts. This research delves into the intricate relationship between climate change and public health, emphasizing the complexities and uncertainties that underscore this critical nexus. While considerable progress has been made in recognizing the links between climate change and health, significant gaps in current research persist. This study underscores the need for further investigation into key areas, including the long-term health impacts of climate change, the mental health consequences, vulnerabilities among specific populations, and healthcare system resilience. Vulnerable populations, such as children, the elderly, low-income communities, and marginalized groups, are at a higher risk and require tailored interventions. Mental health effects, including anxiety, depression, and post-traumatic stress disorder (PTSD), constitute an emerging area of concern that merits comprehensive investigation. Furthermore, healthcare systems must enhance their resilience and preparedness to respond to climate-related health challenges effectively. Interdisciplinary collaboration between researchers, policymakers, healthcare professionals, and communities is crucial for a comprehensive approach to this issue. International cooperation is equally vital, given the global nature of climate change. Policymakers must prioritize evidence-based policies that consider the evolving challenges of climate change on public health and promote health equity. Elevating public awareness and climate literacy is essential to empower individuals and communities to take proactive measures. This research underscores the urgency of addressing the complex interplay between climate change and health and provides a roadmap for future research and policy development to safeguard public health in a changing climate